An IN VIVO EVALUATION OF COMBRETUM INDICUM FLOWER METHANOLIC EXTRACT AS OINTMENT FOR BURN WOUND ON MALE MICE - Haroh, Istik; Aryani, Retno; Rosadi, Imam; Nugroho, Rudy Agung (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Burns that are not treated properly can be dangerous, even can lead to death. Combretum indicum is reported to have anti-inflammatory, antibacterial, and high antioxidant activities, making it effective in healing dermal wounds. This study aimed to evaluate the wound healing effect of C. indicum flower methanolic extract on burn wound model in male mice. A total of 36 adult male mice were randomly assigned to 6 groups namely Negative control (I) without treatment; Positive Control I (II) with Burnazin treatment; Positive control II (III) with Vaseline treatment; Treatment group I (IV) with 25% concentration of C. indicum flower methanolic extract ointment; Treatment group II (V) with 50% concentration of C. indicum flower methanolic extract ointment; Treatment group III (VI) with 75% concentration of C. indicum flower methanolic extract ointment. Mice were treated daily for 20 days, and wound areas were observed every 2 days. Hydroxyproline level and total DNA content were tested on day-11. Skin tissue was analysed histologically. The results indicate that C. indicum flower extract accelerate wound healing process and repair the damaged skin tissue by accelerate the Proliferative phase.